Enhancement of electrical characteristics and stability of self-patterned In–Zn–O thin-film transistors based on photosensitive precursors - Kim, Hee Jun (Sci Rep, 2020)
We report a novel self-patterning method for solution-processed indium zinc oxide (IZO) thin films based on photosensitive precursors. This approach is an alternative and evolutionary approach to the traditional photoresist patterning techniques. Chelate bonds between metal ions and β-diketone compounds in ultraviolet light-exposed IZO solutions provided intrinsic photosensitivity, which resulted in a solubility difference between exposed and non-exposed regions. This difference enabled self-patterning of the IZO for thin-film transistor (TFT) fabrication. Compared with previously reported self-patterning methods based on photosensitive activators, our self-patterned IZO TFTs based on photosensitive precursors displayed excellent electrical characteristics and stability. The field-effect mobility increased from 0.27 to 0.99 cm(2)/Vs, the subthreshold swing decreased from 0.54 to 0.46 V/dec, and the threshold voltage shift under a positive bias stress test (1,000 s) improved from 9.32 to 1.68 V. The photosensitive precursor played a key role in these improvements permitting fewer organic species which act as defect sites after metal oxide formation. Consequently, our approach compares favorably with that of conventional fabrication process using photoresist in terms of its simplicity, cost efficiency, and electrical performance.